Varför behövs vävnadsdonation? - Malm, Torsten (Socialmedicinsk tidskrift, 2007)
Vävnadsdonation är en förutsättning för transplantation av hjärtklaffar, hornhinnor, hörselben, hud och benvävnad. Detta kräver att det finns väl genomtänkta och inarbetade rutiner så att vävnadsdonatorer identifieras i tid, vävnaderna tillvaratas, preserveras och lagras och kan förmedlas till patienter med svåra sjukdomstillstånd, där det många gånger inte finns några andra alternativ till behandling. En välfungerande vävnadsbanksorganisation ofta med en komplicerad logistik är nödvändig. Säkerhet och hög kvalité i vävnadshanteringen är förutsättningar för en framgångsrik transplantationsverksamhet. Nedan beskrivs kortfattat hur vävnadsdonation är utformad i Sverige. Tissue donation is a prerequisite for tissue transplantation. In Sweden 1000 patients are in need of a tissue transplantation yearly. The most common transplant is the cornea. Heart valves are used mainly for correction of complicated congenital heart disease. Skin is required to save patients life after extensive burns. Ear bones can be transplanted to patients with a deformed ear bone chain. Tissue banks are established at some of the university hospitals, there are five units procuring cornea, two for heart valves and one for ear bones. Tissues are retrieved from multi-organ donors through the organ transplantation program and from departments of forensic medicine and pathology. The only integrated tissue bank preserving and delivering different tissues such as heart valves, corneas and ear bones is at the University Hospital in Lund. Sweden is self-sufficient in procurement of tissues. There is some export of tissues to other Scandinavian countries and also to Europe. Waiting lists for cornea transplantation remain long. For heart valves and ear bones there are no waiting lists due to tissue availability. Key words: tissue bank, tissue transplantation, tissue donation, homograft, heart valves, corneas.